Revitalizing the Library OPAC: Interface, Searching, and Display Challenges - Mi, Jia; Weng, Cathy (Information Technology and Libraries, 2008)
The behavior of academic library users has drastically changed in recent years. Internet search engines have become the preferred tool over the library online public access catalog (OPAC) for finding information. Libraries are losing ground to online search engines. In this paper, two aspects of OPAC use are studied: (1) the current OPAC interface and searching capabilities, and (2) the OPAC bibliographic display. The purpose of the study is to find answers to the following questions: Why is the current OPAC ineffective? What can libraries and librarians do to deliver an OPAC that is as good as search engines to better serve our users? Revitalizing the library OPAC is one of the pressing issues that has to be accomplished.